Gambaran Toxic Friendship Di Kalangan Remaja Akhir Universitas X, Badung, Bali - Ida Ayu, Mas saharani pramuditya; Dewi, Ni Nyoman Ari Indra; Cokorda, Tesya Kirana (JURNAL PSIKOLOGI MANDALA, 2025)
Abstrak. This study aims to describe the phenomenon of toxic friendship among late adolescents at University X, Badung, Bali. A toxic friendship is an unhealthy relationship characterized by manipulative and domineering behavior, a lack of empathy, and prolonged emotional pressure. This study employs a qualitative approach using the phenomenological method to explore the subjective experiences of students aged 18–21 who have experienced psychologically harmful friendships. Data were collected through in-depth interviews and observations of four primary informants and supporting informants. The results of the study indicate that toxic friendships arise due to low self-confidence, excessive emotional attachment, social pressure, and academic demands. The impacts felt include stress, social anxiety, overthinking, decreased enthusiasm, loss of motivation to study, and even the desire to withdraw from social environments or drop out of college. These findings emphasize the importance of awareness of healthy boundaries in friendships and the need for educational institutions to support the creation of a positive social environment to maintain students' psychological well-being.